A hydrogel fibril network membrane with high-flux oil-in-water emulsion separation - Hang Song; Kuiling Li; Qinyi Liu; Zimou Liu; Lili Xu; Yong Zhang; Jun Wang (Chemical Engineering Journal, 2026)

Nutrient-heavy metal risk linkages and their differentiated driving mechanisms in sediments of a subtropical drinking water reservoir, South China - Ronghui Li; Kuiling Huang; Kaibang Xiao; Wei Liu (Environmental Pollution, 2026)

Interfacial heterogeneous electro-Fenton membrane distillation for risk-controlled concentration of high-salinity coal-chemical wastewater - Hongxin Liu; Kuiling Li; Lin Fang; Yang Yao; Zhigang Dan; Jun Wang (Journal of Environmental Sciences, 2026)

Dual-stretched expanded PTFE hollow fiber membranes for bubble-free ozonation and catalyst recovery in advanced oxidation process - Jiahui Ren; Qinyi Liu; Tiancheng Chu; Dan Qu; Kuiling Li; Yong Zhang; Jun Wang (Journal of Environmental Chemical Engineering, 2026)

High-efficiency solar-driven photothermal membrane distillation via permeate-side interfacial heating - Qian Yu; Mengfei Xie; Rong Chen; Kuiling Li; Liqiu Zhang; Bo Pan; XueJun Pan; Junhui Zhang; Dan Qu (Desalination, 2026)

Batch-modified Janus membranes via in-membrane-module interfacial polymerization for robust membrane stripping of ammonia from coking wastewater - Kuiling Li; Jiayue Qin; Hang Song; Yong Zhang; Lili Xu; Huazhang Zhao; Dan Qu; Jun Wang (Water Research, 2025)

Ultra-low energy consumption treatment of high-salinity wastewater via novel membrane contactor-forward osmosis process - Zhichao Zhao; Yong Zhang; Tiancheng Chu; Kuiling Li; Hang Song; Xiaohui Wu; Jun Wang (Chemical Engineering Journal, 2025)

Climate‐Driven Variability in Flowering Phenology Changes Across Subtropical Mountains: Traits, Elevation Shifts, and Biogeographic Patterns - Kuiling Zu; Zhiheng Wang; Fusheng Chen; Jonathan Lenoir; Xiangmin Fang; Fangchao Wang; Wensheng Bu; Jianjun Li; Yuan Luo; Yunyun Wang; Wenqi Song (Global Change Biology, 2025)
Flowering phenology has major impacts on physiological processes, survival, and reproductive success in angiosperms, serving as a critical biological indicator of climate change impacts. However, changes in flowering phenology and their determinants in subtropical montane ecosystems remain poorly quantified at continental extents. Here we investigated the determinants of flowering phenology shifts over the past century across 11 subtropical mountains in China. Based on century‐long herbarium collections of 784 flowering plant species in these mountains, we first used linear regression models to assess the magnitude and direction of changes in flowering time for each species in each mountain separately. Then, we investigated the underlying drivers of changes in flowering time, including climate changes, species traits as well as changes in species elevation range size. Our analyses revealed an average advancement in flowering phenology of 3.8 days per decade, though marked regional disparities emerged: flowering times were advanced in southeastern mountains but delayed in southwestern ones. Climate change, species functional traits, and mountain properties all had significant effects on the observed changes in flowering time. Notably, the flowering time of lowland and non‐native plants was advanced more than that of alpine and native plants. A key finding was the negative correlation between flowering time changes and elevational range expansions, supporting the hypothesis that phenological plasticity facilitates range adjustments under environmental change. These findings demonstrate that flowering phenological responses are context‐dependent, mediated by complex biotic–abiotic interactions. Our study provides the first biogeographical assessment of flowering phenology shifts in subtropical Asian mountains, offering critical insights for predicting ecosystem stability and informing biodiversity conservation strategies under ongoing climate change.

Development of expanded polytetrafluoroethylene hollow fiber membranes for membrane Fenton oxidation in wastewater treatment - Yong Zhang; Tiancheng Chu; Kuiling Li; Hongxin Liu; Zhichao Zhao; Xiaohui Wu; Jun Wang (Journal of Hazardous Materials, 2025)

Controllable H2S supply via membrane contactors for safe and efficient arsenic precipitation from acidic wastewater - Tiancheng Chu; Yong Zhang; Linghao Kong; Kuiling Li; Zhichao Zhao; Lili Xu; Xiaohui Wu; Jun Wang (Journal of Hazardous Materials, 2024)

Response of tree growth to nutrient addition is size dependent in a subtropical forest - Bin Liu; Cancan Zhang; Jun Deng; Bowen Zhang; Fusheng Chen; Wei Chen; Xiangmin Fang; Jianjun Li; Kuiling Zu; Wensheng Bu (Science of The Total Environment, 2024)

A novel electro-Fenton hybrid system for enhancing the interception of volatile organic compounds in membrane distillation desalination - Hongxin Liu; Kuiling Li; Kunpeng Wang; Zhiyong Wang; Zimou Liu; Sichao Zhu; Dan Qu; Yu Zhang; Jun Wang (Journal of Environmental Sciences, 2024)

Global multifaceted biodiversity patterns, centers, and conservation needs in angiosperms - Ao Luo; Yaoqi Li; Nawal Shrestha; Xiaoting Xu; Xiangyan Su; Yichao Li; Tong Lyu; Kilara Waris; Zhiyao Tang; Xiaojuan Liu; Luxiang Lin; Yongsheng Chen; et al. (Science China Life Sciences, 2024)

Fenton pretreatment to mitigate membrane distillation fouling during treatment of landfill leachate membrane concentrate: Performance and mechanism - Zhichao Zhao; Yong Zhang; Ling Yu; Deyin Hou; Xiaohui Wu; Kuiling Li; Jun Wang (Water Research, 2023)

Nitrogen addition improves drought tolerance in Camellia japonica (Naidong) seedlings - Cuiju Liu; Jinlong Xie; Mingyan Li; Yingkun Sun; Xiaolei Jiang; Yuwu Li; Jibo Jiao; Kuiling Wang; Qinghua Liu; Xiao Guo (Flora, 2023)

Highly efficient nitrobenzene removal by coupling electrochemical filtration with a microbial electrolysis cell - Jingjing Guo; Kuiling Li; Zhiyong Wang; Dan Qu; Ping Dang; Jun Wang (Journal of Environmental Chemical Engineering, 2023)

A new insight into the low membrane fouling tendency of liquid-liquid hollow fiber membrane contactor capturing ammonia from human urine - Junhui Zhang; Kuiling Li; Mengfei Xie; Qi Han; Li Feng; Dan Qu; Liqiu Zhang; Ke Wang (Water Research, 2023)

Interface adsorption enhanced the membrane contact ozonation: A new strategy to tune the trade-off between micropollutant abatement and bromate formation - Zhiyong Wang; Kuiling Li; Jingjing Guo; Hongxin Liu; Zimou Liu; Yong Zhang; Jun Wang (Chemical Engineering Journal, 2023)

Genetic diversity and population genetic structure of Neillia incisa in China: implications for genetic conservation - Cuiping Zhang; Gangyu Sun; Hai Wang; Xinqiang Jiang; Wei Li; Xiaoman Xie; Yizeng Lu; Kuiling Wang (Trees, 2021)

RhNAC31, a novel rose NAC transcription factor, enhances tolerance to multiple abiotic stresses in Arabidopsis - Aiqin Ding; Shaocui Li; Wei Li; Qing Hao; Xueli Wan; Kuiling Wang; Qingchao Liu; Qinghua Liu; Xinqiang Jiang (Acta Physiologiae Plantarum, 2019)

The Novel Rose MYB Transcription Factor RhMYB96 Enhances Salt Tolerance in Transgenic Arabidopsis - Xinqiang Jiang; Shaocui Li; Aiqin Ding; Zhujun Zhang; Qing Hao; Kuiling Wang; Qingchao Liu; Qinghua Liu (Plant Molecular Biology Reporter, 2018)

Morphogenesis and global analysis of transcriptional profiles of Celastrus orbiculatus aril: unravelling potential genes related to aril development - Kuiling Zu; Jianxia Li; Shubin Dong; Yunyu Zhao; Shenjian Xu; Zhixiang Zhang; Liangcheng Zhao (Genes & Genomics, 2017)